Alternative Strategies for Identifying the Link Between Unemployment and Crime - Levitt, Steven D. (Journal of quantitative criminology, 2001)
National-level time series data are a crude tool for distinguishing between two alternative behavioral explanations for a link between unemployment and crime. Consequently, inferences drawn from aggregate time series estimates are likely to be misleading. A more fruitful approach to learning about the link between unemployment and crime would be to utilize a menagerie of different methodological approaches such as cross-section and panel data analysis of less geographically aggregated areas, natural experiments, international data, individual-level data, and ethnography.